(untitled) (Journal of Dhaka Medical College, 2021)
Osteoarthritis (OA) is by far the most common form of arthritis characterized by focal loss of articular cartilage, subchondral osteosclerosis, osteophyte formation at the joint margin, and remodeling of joint contour with enlargement of affected joints. This randomized, clinical trial aimed to compare the effectiveness of Platelet Rich Plasma (PRP) and Hyaluronic Acid (HA) as individual treatments and PRP in combination with HA in the treatment of mild to moderate knee Osteoarthritis (OA). The study was conducted among 89 patients with mild to moderate knee osteoarthritis in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Patients were randomly allocated to one of the three interventions: HA (n=30), PRP (n=30), or HA+PRP (n=29). Patients in HA group received 3 intra-articular knee injections with 1 week interval while patients in PRP group and PRP+HA group received 2 intra-articular knee injections with 2 week interval. Functional outcome of the treatment were evaluated using the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Visual Analogue Scale (VAS) questionnaire at baseline and after 1,3,6 and 9 months of treatment. Majority of the patients in all groups were female where mean age of the patients were about 50 years. Pain scores in VAS scale significantly reduced in PRP group when compared to HA group and also in PRP+HA when compared to HA group which persist till nine months (p<0.05). No significant statistical difference was found in VAS scores between PRP and PRP+ HA group. WOMAC pain scores also significantly reduced in PRP group when compared to HA group and also in PRP+HA when compared to HA group (p<0.05). WOMAC stiffness significantly reduced in PRP+ HA group when compared to HA group at three month (p<0.001) and at six month (p=0.011). At nine month, physical activity scores significantly reduced in PRP group compared to HA group (p=0.002) and in PRP+HA when compared to HA group (p<0.001). No significant reduction was observed in WOMAC scores when the outcome of PRP+HA was compared with PRP alone. PRP provides better functional outcome than HA. The combination of PRP and HA also provides better outcome than HA alone but does not provide better outcome than PRP alone. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 172-178